INCREASING STUDENT LEARNING OUTCOMES OF EXCRETION SYSTEM MATERIALS THROUGH THE APPLICATION OF THE PROBING PROMPTING MODEL IN CLASS VIII C - Titik Wasiati (Jurnal Scientia, 2021)
Science subjects _ excretion system material in junior high school is a subject that focuses on student competence in understanding, analyzing and evaluating the process of excretion. Student learning outcomes of SMP Negeri 2 Gondang class VIII C , seen from the results of the daily test scores, found that many students did not complete the Minimum Completeness Criteria (KKM) and did not complete their studies. The KKM in the school is 70 and learning completeness is said to be successful if there is a change in behavior of approximately 75%. Observation results obtained daily class test scores, which were incomplete in learning to achieve a completeness percentage of 60%. Based on this description, it shows that the learning outcomes of the excretory system material in class VIII C of SMP Negeri 2 Gondang can be categorized as not good. To improve student learning outcomes on excretory system material , a classroom action research was conducted which consisted of two cycles. Each cycle consists of the stages of planning, implementing, observing and reflecting. The subjects of this study were students of SMP Negeri 2 Gondang Class VIII C academic year 20 19/20 20 consisting of 34 students . The data collection instruments in this study were evaluation questions for the cognitive domain which were carried out at the end of each cycle and observation sheets for the affective and psychomotor domains. Based on the results and discussion it can be concluded that learning using demonstration models combined with projects, can provide convenience for teachers in learning, make learning centered on students, complete learning outcomes, and can teach and train students' character behavior. The implementation of lesson plans was in good category with an average score of 3.63 in the first cycle and 3.81 in the second cycle. Student activity reached 86.46% in the first cycle and rose to 93.33%. In the aspect of scientific behavior both cycles are in the good category. Completeness of learning outcomes also shows an increase, from 70.59% in the first cycle to 91.18% in the second cycle .